Integration of ICT-Pedagogy for Senior High School Students: Pre-service Teachers’ TPACK (Technological Pedagogical Content Knowledge) - Fatahillah Erfan; Sulisyaningsih Sulisyaningsih; Abd. Syakur (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aimed to identify pre-service teachers who are ready to integrate technology into their classrooms. The assumption is that pre-service teachers' characteristics like Technological Pedagogical Content Knowledge (TPACK) are influenced by their teacher training. Preservice teachers were clustered based on their TPACK, a typical set of ICT-related characteristics (general ICT attitudes, attitudes towards ICT in education, ease of use and ICT self-efficacy), and perceived support from their training institution. A random sample of 50 senior high school pre-service teachers from SMA Al-Iftitahiyah in Sumenep was used in this mixed-method research. The results also showed that most participants understood TPACK and had ideas for implementing it in their classrooms. Pre-service teachers' (PTs) perceptions of TPACK in teaching and learning is expected. This study also has implications for experts interested in pre-service teachers' understanding of teaching with technology.